Design and Efficiency Enhancement Studies of Periodically Dielectric Loaded W-Band Gyro-TWT Amplifier - Akash; Thottappan M. (My University, 2025)
In this article, design, simulation, and efficiency improvement of ${W}$ -band gyrotron traveling wave tube (gyro-TWT) amplifier operating at fundamental TE01 mode have been presented. A triode-type magnetron injection gun (MIG) has been designed and optimized for the desired quality of electron beam with a minimum spread 2% with velocity ratio 1.12 to improve the electronic efficiency of gyro-TWT. Parasitic modes in gyro-TWT have been suppressed by employing a periodic dielectric loading in the RF interaction circuit. The simulated amplifier developed an output power of 203 kW in fundamental TE01 mode with an electronic efficiency 29% and power gain 57 dB for a nonspread gyrating electron beam. To improve the overall efficiency of gyro-TWT, a single-stage depressed collector has been designed as a spent electron beam recovery system. The proposed collector has enhanced the overall efficiency of gyro-TWT to 48%. © 1963-2012 IEEE.